2021
DOI: 10.1007/s00439-020-02248-x
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing in normal and pathological human placentas is correlated to genetic variants

Abstract: Two major obstetric diseases, preeclampsia (PE), a pregnancy-induced endothelial dysfunction leading to hypertension and proteinuria, and intra-uterine growth-restriction (IUGR), a failure of the fetus to acquire its normal growth, are generally triggered by placental dysfunction. Many studies have evaluated gene expression deregulations in these diseases, but none has tackled systematically the role of alternative splicing. In the present study, we show that alternative splicing is an essential feature of pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…While the placenta is not affected by drugs, which can have a satisfactory effect on the perinatal final maternal and infant outcome [ 8 , 9 ]. Labetalol, as a first-line drug for reducing blood pressure in PIH, is mainly due to its mild effect on lowering blood pressure and does not affect placental blood flow, which will not lead to symptoms such as low blood pressure and rapid heart rate [ 10 , 11 ]. Therefore, the present study outlines the clinical effectiveness of nifedipine and magnesium sulfate combined with labetalol in PIH, to guide clinical decision making in the selection of a better treatment plan.…”
Section: Introductionmentioning
confidence: 99%
“…While the placenta is not affected by drugs, which can have a satisfactory effect on the perinatal final maternal and infant outcome [ 8 , 9 ]. Labetalol, as a first-line drug for reducing blood pressure in PIH, is mainly due to its mild effect on lowering blood pressure and does not affect placental blood flow, which will not lead to symptoms such as low blood pressure and rapid heart rate [ 10 , 11 ]. Therefore, the present study outlines the clinical effectiveness of nifedipine and magnesium sulfate combined with labetalol in PIH, to guide clinical decision making in the selection of a better treatment plan.…”
Section: Introductionmentioning
confidence: 99%
“…Another direction for future work is the assessment of the specific effects of the short isoforms of UCA1 that appear to be specifically modified when fusion occur. To note, we have recently demonstrated that alternative splicing is a general feature of placental disease, affecting hundreds of genes ( Ruano et al, 2021 ). This could be achieved by lentiviral transformation of the cell lines, or even primary cultures with this short isoform.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Ruano et al (2021) published the first systematic analysis of alternative splicing in third trimester placentas by microarray comparing preeclamptic and intra uterine growth restricted (IUGR) placentas to healthy controls. In their study, genes differentially spliced in preeclamptic placentas were predominantly associated with extracellular matrix organization pathways, genes differentially spliced in IUGR placentas were associated with hypoxia and hormone metabolism, while preeclampsia and IUGR both were associated with exocytosis.…”
Section: Discussionmentioning
confidence: 99%